2005
DOI: 10.1002/jbm.a.30345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soluble metals on human peri‐implant cells

Abstract: Despite reports associating tissue necrosis with implant failure, the degree to which processes, such as metal toxicity, negatively impact implant performance is unknown. We evaluated representative human peri-implant cells (i.e., osteoblasts, fibroblasts, and lymphocytes) when challenged by Al+3, Co+2, Cr+3, Fe+3, Mo+5, Ni+2, and V+3 chloride solutions (and Na+2 as a control) over a wide range of concentrations (0.01-10.0 mM). Cell responses were measured using proliferation assays, viability assays, and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 45 publications
3
84
0
4
Order By: Relevance
“…41 In a recent study using both primary and established cells Cr and Al are classified as "moderately to mildly toxic" for osteoblasts, as some effects on cells were assessed at a concentration around 5mM. 42 Our results confirm that osteoblast-like cells can easily bear ion release from ALUSI alloys.…”
Section: Discussionsupporting
confidence: 67%
“…41 In a recent study using both primary and established cells Cr and Al are classified as "moderately to mildly toxic" for osteoblasts, as some effects on cells were assessed at a concentration around 5mM. 42 Our results confirm that osteoblast-like cells can easily bear ion release from ALUSI alloys.…”
Section: Discussionsupporting
confidence: 67%
“…Okazaki et al 25) reported that metallic ions such as Ti, Zr, Sn, Nb, and Ta had evidently no harmful effects on the growth ratios of cells however, Al and V ions presented lower rate as compared to that of titanium ion. Hallab et al 26) . also showed that cobalt (Co) and V released from Co-and Ti-based alloys respectively, could mediate cell cytotoxicity in the joint periprosthetic milieu.…”
Section: Rt-pcr Gene Expression Analysismentioning
confidence: 99%
“…Among titanium alloys employed as metallic implant materials, Ti-6Al-4V has been widely used in dental and medical fields. Although this alloy is still widely used in dental and medical fields, some concerns such as toxicity of V and Al and high elastic modulus, have been reported [6][7][8] . Surface roughness and topography can greatly affect the proliferation and protein synthesis of osteoblast cells that are cultured on a metal substrate characteristics in the healing of bone 21,22) .…”
Section: Surface Characterization and Roughness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated that below 0.01 mM, neither Zr nor Mo was toxic to osteoblasts and fibroblasts. 5,55 In addition, the biocompatibility of Zr-Mo alloys was primarily evaluated by culturing L-929 cells and MG 63 cells in their extraction media and positive results were obtained, indicating an excellent in vitro biocompatibility.…”
Section: Biocompatibility Of Zr-mo Alloys and Their Promises As Medicmentioning
confidence: 99%